REFLECTION OF THE PROPHET'S HADITH IN TOLSTOY'S WORKS - Sagdiev Khabibullo (Modern American Journals, 2025)
This article explores the reflection of Prophet Muhammad’s hadiths in the works of Lev Tolstoy, particularly in Circle of Reading and The Words of Muhammad. Through an examination of Tolstoy’s religious evolution, correspondence with Muslim thinkers, and selection of Islamic sayings, the study clarifies misconceptions about his alleged conversion to Islam. It reveals how Tolstoy viewed hadiths as moral teachings aligning with his philosophical and spiritual ideals.
Keywords: Tolstoy, hadith, islam, philosophy, religion, ethics, spirituality